Biocontrol Potential of Paecilomyces Lilacinus against Plant-Parasitic Nematodes: In Vitro - Bhairappa A. A.,; Dama L. B.,; Shelke R. R., (International Journal of Scientific Research in Science and Technology, 2026)
Plant-parasitic nematodes (PPNs), perdominantly Meloidogyne spp. (root-knot nematodes), are among thse most destructive hidden enemies of agriculture, causing substantial yield losses in a wide range of crops. The present study was undertaken to evaluate the antagonistic potential of the rhizosphere fungus Paecilomyces lilacinus against plant-parasitic nematodes through in vitro assays and microscopic observations as eco-friendly approach to overcome pollution spreading by chemical nematocidal preparation. P. lilacinus was isolated from rhizosphere soil of healthy crop plants and cultured on Potato Dextrose Agar (PDA). Nematodes were obtained from infected root samples and exposed to fungal inocula. Dual culture and parasitism assays were performed to assess the interaction between the fungus and nematodes. Microscopic examinations were carried out to document fungal penetration of nematode eggs and juveniles, along with associated structural deformations. The fungal isolate exhibited rapid growth on PDA and demonstrated strong antagonistic activity against nematodes. Microscopic evidence revealed direct hyphal penetration of nematode eggs and cuticles, accompanied by deformation, immobility, and mortality of juveniles. In vitro assays confirmed a significant reduction in nematode survival and egg hatchability in fungal-treated sets compared to controls. The findings highlight P. lilacinus as an efficient nematophagous fungus with dual benefits of nematode suppression and potential plant growth promotion. Its antagonistic efficacy, combined with its eco-friendly and non-toxic nature, positions P. lilacinus as a promising alternative to chemical nematicides in integrated nematode management strategies for sustainable agriculture.
Keywords: Paecilomyces lilacinus; Purpureocillium lilacinum; Plant-parasitic nematodes; Root-knot nematodes; Meloidogyne spp.; Biocontrol; Nematophagous fungi; Rhizosphere microorganisms; Microscopic evidence; Sustainable agriculture